2005
DOI: 10.1051/0004-6361:20053201
|View full text |Cite
|
Sign up to set email alerts
|

Preferred sunspot longitudes: non-axisymmetry and differential rotation

Abstract: Abstract.As recently found, the distribution of sunspots is non-axisymmetric and spot group formation implies the existence of two persistent active longitudes separated by 180• . Here we quantitatively study the non-axisymmetry of sunspot occurrence. In a dynamic reference frame inferred from the differential rotation law, the raw sunspot data show a clear clustering around the persistent active longitudes. The differential rotation describing the dynamic frame is quantified in terms of the equatorial angular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
93
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(109 citation statements)
references
References 12 publications
14
93
2
Order By: Relevance
“…By filtering the data with this limit, 53% of the CRs shows exactly one significant longitudinal belt; meanwhile, the remaining fraction of the data did not show strong in-homogeneous properties. Many studies have adressed the existence of the co-dominant longitude that has a phase shift of 180°from the dominant peak (Usoskin et al 2005;Zhang et al 2007Zhang et al , 2011a. However, we have found that the secondary AL is not, or is hardly detectable, after applying a high-pass filter to sort out the insignificant peaks.…”
Section: The Methods Of Tracking Almentioning
confidence: 62%
See 1 more Smart Citation
“…By filtering the data with this limit, 53% of the CRs shows exactly one significant longitudinal belt; meanwhile, the remaining fraction of the data did not show strong in-homogeneous properties. Many studies have adressed the existence of the co-dominant longitude that has a phase shift of 180°from the dominant peak (Usoskin et al 2005;Zhang et al 2007Zhang et al , 2011a. However, we have found that the secondary AL is not, or is hardly detectable, after applying a high-pass filter to sort out the insignificant peaks.…”
Section: The Methods Of Tracking Almentioning
confidence: 62%
“…DISCUSSION AND CONCLUSION Zhang et al (2008) found that the ALs with half widths of 20°-30°contain 80% of C-flares during the solar minimum and X-flares during solar maximum. The AL was defined by the dynamic reference frame, introduced by Usoskin et al (2005). Hence, their study assumes two detectable and equally strong ALs, separated by 180°.…”
Section: Temporal Properties Of Solar Flares Near Almentioning
confidence: 99%
“…Follow-up studies concerning the preferred locations (longitudes) of sunspot formation delivered inconsistent and partly contradictory results. Even today, the possible number, migration, life times, longterm behavior and the particular method to track them remain a subject of debate (see Berdyugina and Usoskin 2003;Usoskin et al 2005;Pelt et al 2006;Usoskin et al 2007;Weber et al 2013;Gyenge et al 2014). …”
Section: Cyclic Changes Of the Coronal Magnetic Fieldmentioning
confidence: 99%
“…-aggregated data (daily Wolf numbers) and correlation analysis (Bogart 1982); -raw heliographic longitudes and longitude-wise binning (Trotter & Billings 1962;Warwick 1965); -transformed (using trial rotation velocity) longitudes and χ 2 statistic (Bai 1987); -transformed (using latitude-dependent rotation velocities) longitudes and pattern matching (Usoskin et al 2005;Pelt et al 2006, hereafter PBKT); -spherical harmonic decomposition and time series analysis of mode amplitudes, phases and phase-walks (Juckett 2003).…”
Section: Introductionmentioning
confidence: 99%